THE IMPLEMENTATION OF THE STRENGTHENING CHARACTER EDUCATION IN SDN 09 MATARAM CITY, NTB - Nur Listiawati Chaironi (LPPM Universitas Negeri Yogyakarta, 2019)
This study is a qualitative one that attempts to illustrate the implementation of the 5 main values of Strengthening Character Education (religious, nationalist, self-reliance, mutual cooperation and integrity) and other Core values that are prioritized in the target school. This is a case study in one of the primary schools in Mataram City, Nusa Tenggara Barat, Indonesia. The study used an inductive reasoning approach. Planting and implementing the values has been done through various themes or activities programs. Some obstacles emerged in the implementation activities and had been solve by rearranging schedule, communication, coordination between school’s elements and parents, adjustment between the concept of Curriculum 2013 and Strengthening Character Education, therefore besides 4C (Critical Thinking, Communication skill, Creativity and Innovation, and Collaboration), it is better to consider to increase 3C (Communication, Coordination and Cooperation) in Character Education. In implementing this character education, there are supporting factors such as principal’s leadership, other elements of the school, and school network.